Brick and Pottery Kilns in Mang Thit, Vinh Long: Local Knowledge and Community of Practice in the Mekong Delta, Vietnam - Duc, On Tri; Singyabuth, Supachai; Tuyen, Nguyen Thi Ngoc (Journal of Cultural Analysis and Social Change, 2025)
This research examines qualitative methods and primary research that evaluates local knowledge and the "community of practice" (CoP). The Mekong Delta of Vietnam, located in Mang Thit, Vinh Long, has a rich history of traditional brick and pottery manufacturing. The goal of this study is to monitor the historical formation of the craft village, analyze mechanisms of intergenerational knowledge transfer, and consider socio-economic development. This study shows that the region's natural geology, particularly the amount of clay surrounding the Co Chien River, has a dense canal system that is one of the essential factors for Mang Thit's foundation, as well as key hubs for brick and pottery manufacturing during the colonial period. CoP operated in this craft village by combining customary methods with experiential learning and incremental innovation. The knowledge and skills of this approach are passed down through families and artisan groups. However, these industries face difficulties due to urbanization, limited resources, stricter environmental regulations, and market shifts, resulting in reduced production, a lack of workforce, and weakened traditional practices. Artisans, businesses, and local authorities are developing adaptive ideas by combining them with sustainable development policies to enhance craft innovation and cultural tourism. This research promotes an expanded discussion of cultural heritage, rural adaptability, and the resilience of local knowledge systems in the face of socio- environmental transformations.